2023
DOI: 10.3390/cancers15194769
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-Invasive Secondary Cytoreduction in Recurrent Ovarian Cancer

Camilla Certelli,
Silvio Andrea Russo,
Luca Palmieri
et al.

Abstract: The role of secondary cytoreductive surgery (SCS) in the treatment of recurrent ovarian cancer (ROC) has been widely increased in recent years, especially in trying to improve the quality of life of these patients by utilising a minimally-invasive (MI) approach. However, surgery in previously-treated patients may be challenging, and patient selection and surgical planning are crucial. Unfortunately, at the moment, validated criteria to select patients for MI-SCS are not reported, and no predictors of its feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Sanna et al reported a case series of MIS nodal relapse asportation up to 8 cm, demonstrating that MIS for ILNR in gynecological malignancies may be a feasible, safe and effective option in terms of oncological outcomes, even for large tumors [40]. Recently, Certelli et al published a review specifically about the role of SCS in the treatment of recurrent ovarian cancer, showing that a minimally invasive approach plays a crucial role in this setting in terms of survival rates and quality of life [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sanna et al reported a case series of MIS nodal relapse asportation up to 8 cm, demonstrating that MIS for ILNR in gynecological malignancies may be a feasible, safe and effective option in terms of oncological outcomes, even for large tumors [40]. Recently, Certelli et al published a review specifically about the role of SCS in the treatment of recurrent ovarian cancer, showing that a minimally invasive approach plays a crucial role in this setting in terms of survival rates and quality of life [41].…”
Section: Discussionmentioning
confidence: 99%